Pragmatic Features In The Utterances Of Male And Female Of Siladangnese - Sri Minda; Sri Minda Murni; T. Tyrhaya Zein (LINGUISTIK TERAPAN, 2015)
The objective of this study is to describe the pragmatic features of tag question and hedge in the utterances of male and female of Siladangnese. The research was designed with qualitative descriptive method. The data were obtained by implementing participant observation and interview. The finding shows that there are two types of pragmatics features of tag question in the utterances of male and female of Siladangnese. Five pragmatic features of hedge in the utterances of male and female of Siladangnese found; a) hedge as a means of protection, b) hedge as a means of certainty, c) hedge as a means of uncertainty, d) hedge as a means of politeness, and e) hedge as a means of limitation. Male Siladangnese tend to utter modal tag as a sign of uncertainty while female Siladangnese tend to utter affective tag as a sign of politeness. One of the pragmatic features of hedge in the utterances of female Siladangnese is a means of politeness, but it was not found in the utterances of male Siladangnese. The total number of tag question and hedge in the utterances of male and female of Siladangnese is different but it did not show a significant differences.   Keywords: Pragmatic feature; tag question; hedge; gender.